Vincetoxicum nakaianum (Asclepiadoideae, Apocynaceae), a new species from Japan for Cynanchum magnificum Nakai, nomen nudum - Ko Mochizuki; Shuichi Nemoto; Jin Murata; Tetsuo Ohi-Toma (PhytoKeys)
Vincetoxicum Wolf is the third largest genus in Asclepiadoideae, and 23 species are distributed in Japan. We discovered that an erect herb species, distributed in the eastern part of the Honshu island, was invalidly named Vincetoxicum magnificum (Nakai) Kitag. based on Cynanchum magnificum Nakai, nomen nudum. Therefore, we presently name this species Vincetoxicum nakaianum K.Mochizuki & Ohi-Toma, and we give a detailed description in this study. Additionally, we provide photographs that demonstrate its ecology and diagnostic characteristics.